Field surveys for natural enemies of banana weevil, Cosmopolites sordidus (Germar) in Indonesia with emphasis on searches for egg and larval parasitoids - Abera-Kalibata, A.M.; Hasyim, A.; Gold, Cliford S.; Driesche, R.V. (2002)
The banana weevil, Cosmopolites sordidus (Germar), is an important pest of highland banana and plantain in Africa. It exists in low densities in its presumed area of origin in Southeast Asia. This suggests the possible existence of effective co-evolved natural enemies that might be useful in a classical biological program against the pest in Africa. Surveys on banana weevil and its natural enemies were under-taken in Indonesia, in 2000 and 2001. Banana weevil incidence was found to be low, 0.6–1.7 adults per trap in West Sumatra and 0.2–0.4 in West Java. Plant damage indices were below 2.2%, a level that would be considered unimportant in Uganda. We collected and reared 25,980 eggs and 3671 larvae, but no parasitism was detected. Phorids (Megaselia sp.) and drosophilids were recovered from larval rearings, but most likely were scavengers. A complex of predators was detected, the most important of which was the histerid Plaesius javanus Erichson. In laboratory tests, adults and larvae of P. javanus attacked 75–88 and 38–53% of banana weevil larvae and pupae, respectively, that had been inserted in plant pieces. In separate tests, P. javanus larvae entered banana weevil tunnels in corms and attacked 70% of the banana weevil larvae in them. Predatory ants, including species of Myrmicinae, Ponerinae, Formicinae, and Dolichoderinae, were found associated with banana plants and residues. Adults of Myopopone castanea Smith (Ponerinae) were directly observed attacking banana weevil larvae in crop residues. The banana weevil, Cosmopolites sordidus (Germar), is an important pest of highland banana and plantain in Africa. It exists in low densities in its presumed area of origin in Southeast Asia. This suggests the possible existence of effective co-evolved natural enemies that might be useful in a classical biological program against the pest in Africa. Surveys on banana weevil and its natural enemies were under-taken in Indonesia, in 2000 and 2001. Banana weevil incidence was found to be low, 0.6–1.7 adults per trap in West Sumatra and 0.2–0.4 in West Java. Plant damage indices were below 2.2%, a level that would be considered unimportant in Uganda. We collected and reared 25,980 eggs and 3671 larvae, but no parasitism was detected. Phorids (Megaselia sp.) and drosophilids were recovered from larval rearings, but most likely were scavengers. A complex of predators was detected, the most important of which was the histerid Plaesius javanus Erichson. In laboratory tests, adults and larvae of P. javanus attacked 75–88 and 38–53% of banana weevil larvae and pupae, respectively, that had been inserted in plant pieces. In separate tests, P. javanus larvae entered banana weevil tunnels in corms and attacked 70% of the banana weevil larvae in them. Predatory ants, including species of Myrmicinae, Ponerinae, Formicinae, and Dolichoderinae, were found associated with banana plants and residues. Adults of Myopopone castanea Smith (Ponerinae) were directly observed attacking banana weevil larvae in crop residues.